A randomised controlled trial of mentalization-based treatment versus structured clinical management for patients with comorbid borderline personality disorder and antisocial personality disorder. Issue 1 (December 2016) - Bateman, Anthony; O'Connell, Jennifer; Lorenzini, Nicolas; Gardner, Tessa; Fonagy, Peter
Abstract Background Antisocial personality disorder (ASPD) is an under-researched mental disorder. Systematic reviews and policy documents identify ASPD as a priority area for further treatment research because of the scarcity of available evidence to guide clinicians and policymakers; no intervention has been established as the treatment of choice for this disorder. Mentalization-based treatment (MBT) is a psychotherapeutic treatment which specifically targets the ability to recognise and understand the mental states of oneself and others, an ability shown to be compromised in people with ASPD. The aim of the study discussed in this paper is to investigate whether MBT can be an effective treatment for alleviating symptoms of ASPD. Methods This paper reports on a sub-sample of patients from a randomised controlled trial of individuals recruited for treatment of suicidality, self-harm, and borderline personality disorder. The study investigates whether outpatients with comorbid borderline personality disorder and ASPD receiving MBT were more likely to show improvements in symptoms related to aggression than those offered a structured protocol of similar intensity but excluding MBT components. Results The study found benefits from MBT for ASPD-associated behaviours in patients with comorbid BPD and ASPD, including the reduction of anger, hostility, paranoia, and frequency of self-harm and suicide attempts, as well as the improvement of negative mood, general psychiatric symptoms, interpersonal problems, and social adjustment. Conclusions MBT appears to be a potential treatment of consideration for ASPD in terms of relatively high level of acceptability and promising treatment effects. Trial registration ISRCTNISRCTN27660668, Retrospectively registered 21 October 2008